자색고구마 분말을 첨가한 소시지의 제조 및 품질 특성 - 정경아(Gyeong A Jeong); 이창주(Chang Joo Lee) (한국식품과학회지, 2024)
본 연구는 소시지에 전분 대신 자색고구마 가루를 함량별로 첨가함으로 나타나는 자색고구마 소시지의 품질 특성에 대해 알아보고자 하였다. 자색고구마 가루를 첨가한 소시지의 색도는 자색고구마 가루 첨가량이 증가할수록 명도와 황색도는 감소하였으나 적색도는 증가하는 경향을 보였으며, 외관 사진에서 동일한경향을 띠었다. 소시지의 pH, 수분함량 측정결과 시료 간의 유의적 차이는 없었으나, 자색고구마 가루 첨가량이 증가할수록 총폴리페놀 함량과 DPPH radical 소거능이 증가하였다. 이는 자색고구마가 가지고 있는 항산화 성분에 의한 것으로 보인다. 자색고구마 함량이 증가할수록 항산화 기능 성분이 증가하였으나 조직감 측정 결과 자색고구마 가루 첨가량이 증가할수록 경도, 탄력성, 응집성, 검성, 씹힘성이 감소하는 것으로 나타났다. 이에 따라 자색고구마 가루 첨가시 적정 함량을 첨가해야 되며, 이는 전분 첨가량의 25% (SP-25)와 50% (SP-50)가 적절한 것으로 보인다. 따라서, 항산화 성분을 많이 함유하는 SP-50 시료가 자색고구마 가루의 적정함량으로 판단된다. This study investigated the quality characteristics of sausages produced by replacing starch, a sub-material of sausages, with 0, 25, 50, and 100% of purple sweet potato (PSP) powder. As the amount of PSP powder added increased, the L* and b* values of sausages with PSP powder decreased, but the a* value increased. This showed the same trend as the appearance. Total polyphenol content and DPPH radical scavenging activity increased as the amount of PSP powder added increased. However, textural properties such as hardness, elasticity, cohesiveness, gumminess, and chewiness decreased as the amount of PSP powder increased. Therefore, the appropriate amount of purple sweet potato added for sausage texture and antioxidant function is considered to be less than 50% of the amount of general starch added. Overall, sausages supplemented with purple sweet potato show potential as a functional food ingredient with antioxidant properties. KCI Citation Count: 0